DIGITAL ANIMATION IN PANCASILA EDUCATION LEARNING: POWTOON MEDIA INNOVATION TO ENHANCE CIVIC KNOWLEDGE AND UNITY VALUES IN ELEMENTARY SCHOOL STUDENTS - Bahar, Viona Savira; Nurulpaik, Iik; Suprianto, Oki (PIONIR: JURNAL PENDIDIKAN, 2026)
This study aims to analyze the differences in civic knowledge between students using Powtoon digital animation media and students learning through conventional methods, as well as to measure the effectiveness of Powtoon media in improving civic knowledge and the value of unity in elementary school students. The research uses a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The research subjects are the fourth-grade students of SDN Sempu 1, consisting of class IV A as the experimental group and class IV B as the control group. The research instruments are learning outcome tests and student attitude observation sheets. Data were analyzed using the Shapiro-Wilk normality test, Levene's Test for homogeneity, t-tests, and Cohen's d effect size. The research results show a significant difference between students' civic knowledge before and after learning using Powtoon media, with a significance value of p < 0.05. The effect size value of 0.83 indicates that using Powtoon media has a large impact on improving civic knowledge and unity values. Additionally, the observation results indicate that student attitudes and engagement are in the very good category. Thus, Powtoon digital animation media is effectively used as an innovative learning medium in Pancasila Education lessons in elementary school. Keywords: Elementary Education, Civic Knowledge, Digital Animation, Powtoon